Student Preferences for Financial Technology Digital Payment Services - Dhian Rosalina; Kartika Yuliari; Muhammad Rizqi Zati (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2023)
Payment transactions using financial technology products have become a habit for payment transactions today. Fintech is a financial service that uses information technology and can systematically change business models, especially payment transactions. This study aimed to find out how students are interested in using fintech payments. This research was conducted at the Faculty of Economics, Kadiri University, with a total of ninety students as respondents. The analysis technique uses the Hierarchy of Effect Model with the stages of analysis of awareness, knowledge, liking, preference, conviction, and intention. The results of the study show that at each stage the response from respondents to fintech payments and the types of products is high, which means there is already awareness, knowledge, preferences, beliefs, and decisions to use products from fintech payments.